Clinical and genetic heterogeneity in peroneal muscular atrophy associated with vocal cord weakness. Issue 6 (1st December 2002) - McEntagart, M; Dunstan, M; Bell, C; Boltshauser, E; Donaghy, M; Harper, P S; Williams, N; Teare, M D; Rahman, N
Abstract : Background: The peroneal muscular atrophy syndrome is the most common inherited disorder of the peripheral nervous system and has extensive clinical and genetic heterogeneity. Cranial nerve involvement is rare, though there are distinct peroneal muscular atrophy syndromes in which vocal cord paralysis is a characteristic feature. Among these dHMN-VII and HMSN-IIC are clinically similar but are differentiated by sensory involvement in HMSN-IIC. The gene for dHMN-VII, designated DHMNVP, has been localised to chromosome 2q14, but the location of the gene for HMSN-IIC is currently unknown. It has been suggested that dHMN-VII and HMSN II-C are allelic disorders. Objective: To assess the contribution of the dHMN-VII predisposition gene to peroneal muscular atrophy syndromes associated with vocal cord weakness. Methods: Linkage analysis of microsatellite markers at chromosome 2q14 was undertaken on two families, one affected by HMSN-IIC and a second manifesting vocal cord paralysis and sensorineural deafness in addition to distal muscular atrophy. Results: Two-point LOD scores at chromosome 2q14 markers encompassing the DHMNVP gene were negative in both families. Conclusions: These results suggest that at least one further gene predisposing to distal muscular weakness in association with vocal cord paralysis is likely to exist, and that dHMN-VII and HMSN-IIC are unlikely to be allelic disorders. Analyses of further HMSN-IIC families are required to confirm this.